2020
DOI: 10.3389/fpsyg.2020.01002
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Psychological Fitness to Drive for Intoxicated Drivers: Relationships of Cognitive Abilities, Fluid Intelligence, and Personality Traits

Abstract: Our study explores the relationships between traffic-psychological driving-related personality traits, fluid intelligence, and cognitive abilities for drivers whose driver license has been revoked due to intoxicated driving (alcohol and/or drugs). We were able to show that high significant impacts on cognitive functions derive from the participants' age and fluid intelligence. In addition, driving-related personality traits like emotional instability, sense of responsibility and self-control contributed signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…First, as observed in recent studies [ 77 ], a significant and negative effect of age was expected on measures of the fitness to drive in both models. Moreover, a gender effect was expected on measures of resilience of attention in favor of females and on motor speed in favor of males [ 81 ].…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…First, as observed in recent studies [ 77 ], a significant and negative effect of age was expected on measures of the fitness to drive in both models. Moreover, a gender effect was expected on measures of resilience of attention in favor of females and on motor speed in favor of males [ 81 ].…”
Section: Introductionsupporting
confidence: 69%
“…Relatively few studies have investigated the relationship between normal or pathological personality traits and cognitive functions related to driving. By using a driving-specific computerized tool (e.g., the Vienna Test System) [ 76 ], Nechtelberger et al [ 77 ] recently investigated the relationship between personality traits, cognitive abilities, and fluid intelligence in drivers with a revoked driving license due to intoxicated driving (alcohol/drug consumption). Authors found that participants with higher emotional instability showed lower hand–eye coordination, poorer selective attention, and poorer resilience of attention, as well as lower perceptual and motor speed, compared with those lower in emotional instability.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations